2023
DOI: 10.1177/15459683221147839
|View full text |Cite
|
Sign up to set email alerts
|

Gait-Adaptability Training in People With Hereditary Spastic Paraplegia: A Randomized Clinical Trial

Abstract: Background and objectives In people with hereditary spastic paraplegia (HSP), reduced gait adaptability is common and disabling. Gait impairments result from lower extremity spasticity, muscle weakness, and impaired proprioception. The aim of this study was to assess the efficacy of a 5-week gait-adaptability training in people with pure HSP. Method We conducted a randomized clinical trial with a cross-over design for the control group, and a 15-week follow-up period after training. Thirty-six people with pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“… 41 ( Tables 2 and 5 ) In one study of people with hereditary spastic paraplegia, people who received C-mill treadmill with AR did not show any improvements in balance, gait or falls. 44 ( Tables 2 and 5 ) Sample sizes ranged from 16 to 68 and were relatively similar between studies that found between group differences and those that did not. Intervention intensity generally ranged from 20 min 3x/week to 60 min 5x/week for four to 8 weeks.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“… 41 ( Tables 2 and 5 ) In one study of people with hereditary spastic paraplegia, people who received C-mill treadmill with AR did not show any improvements in balance, gait or falls. 44 ( Tables 2 and 5 ) Sample sizes ranged from 16 to 68 and were relatively similar between studies that found between group differences and those that did not. Intervention intensity generally ranged from 20 min 3x/week to 60 min 5x/week for four to 8 weeks.…”
Section: Resultsmentioning
confidence: 89%
“… 12 , 18 , 19 , 25 27 ( Table 1 ); 22 studies included adults with chronic neurological conditions (15 pilot case or observational studies studies; 9 11 , 28 – 39 7 experimental studies. 16 , 17 , 40 44 ) (See Table 2 ) Four articles were of orthopedic populations, (1 pilot study 45 3 experimental studies). 46 48 ( Table 3 ) One study examined clinical outcomes of pulmonary function after knee surgery, 49 one study was among women recovering from breast cancer surgery, 50 one study of older women with sarcopenia, 51 and one patient with burns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 126 Although there was speculation that rTMS could be paired with gait training to achieve greater functional improvements, an RCT on gait-adaptability training for HSP patients did not show significant benefits. 128 Notably, an RCT on transcutaneous spinal direct current stimulation (tsDCS), a non-invasive method for modulating spinal cord function, demonstrated reductions in spasticity and is proposed as a complementary strategy for patients not responding to alternative treatments ( Table 4 ). 129 …”
Section: Current and Emerging Therapeutic Targets And Management Stra...mentioning
confidence: 99%